Satellite‐Based Sea Surface Salinity Designed for Ocean and Climate Studies. Issue 11 (22nd November 2021) - Boutin, J.; Reul, N.; Koehler, J.; Martin, A.; Catany, R.; Guimbard, S.; Rouffi, F.; Vergely, J. L.; Arias, M.; Chakroun, M.; Corato, G.; Estella‐Perez, V.; et al.
Abstract: Sea Surface Salinity (SSS) is an increasingly used Essential Ocean and Climate Variable. The Soil Moisture and Ocean Salinity (SMOS), Aquarius, and Soil Moisture Active Passive (SMAP) satellite missions all provide SSS measurements, with very different instrumental features leading to specific measurement characteristics. The Climate Change Initiative Salinity project (CCI + SSS) aims to produce a SSS Climate Data Record (CDR) that addresses well‐established user needs based on those satellite measurements. To generate a homogeneous CDR, instrumental differences are carefully adjusted based on in‐depth analysis of the measurements themselves, together with some limited use of independent reference data. An optimal interpolation in the time domain without temporal relaxation to reference data or spatial smoothing is applied. This allows preserving the original datasets variability. SSS CCI fields are well suited for monitoring weekly to interannual signals, at spatial scales ranging from 50 km to the basin scale. They display large year‐to‐year seasonal variations over the 2010–2019 decade, sometimes by more than ±0.4 over large regions. The robust standard deviation of the monthly CCI SSS minus in situ Argo salinities is 0.15 globally, while it is at least 0.20 with individual satellite SSS fields. r 2 is 0.97, similar or better than with original datasets. The correlation with independent ship thermosalinographs SSS further highlights the CCI data set excellent performance, especially near land areas. During the SMOS‐Aquarius period, when the representativity uncertainties are the largest, r 2 is 0.84 with CCI while it is 0.48 with the Aquarius original data set. SSS CCI data are freely available and will be updated and extended as more satellite data become available. Plain Language Summary: Salinity measures the mass of dissolved salts in seawater. Together with temperature and pressure, it determines the seawater density, which is crucial in driving oceanic motions. Low sea surface salinity (SSS) can be the result of freshwater inputs such as rain, river runoffs, and ice melt. In contrast, high SSS often characterize regions of strong evaporation. The salinity imprint of these processes is then carried by ocean currents over long distances and long periods of time. SSS also impacts ocean circulation through its effect on density, and modulates ocean‐atmosphere exchanges of heat and gases. SSS is a hence key variable for ocean and climate studies, both as a passive tracer and as an important actor of oceanic processes. Since 2010, three satellite missions have monitored SSS with an unprecedented spatial and temporal resolution. For the first time, data from these satellites are combined, taking each instrument specific features into account. The resulting data set enables global SSS to be monitored and studied with unprecedented accuracy over the 2010–2019 period, at a 50 km, weekly or monthly resolution. It reveals large SSS signals related to phenomena affecting climate in various parts of the world ocean. Key Points: 2010–2019 Sea Surface Salinity fields built from three satellite missions data sets Monitors sea surface salinity variability at large meso‐ to basin scale with unprecedented accuracy and spatio‐temporal coverage Answers the need for Sea Surface Salinity global fields at higher resolution than 1 month, 1°